The Relationship between Anemia and Helicobacter Pylori Infection in Children - Ancuta Lupu; Ingrith Crenguta Miron; Anca Lavinia Cianga; Andrei Tudor Cernomaz; Vasile Valeriu Lupu; Dragos Munteanu; Dragos Catalin Ghica; Silvia Fotea (MDPI AG, 2022)
(1) Background: Many studies suggest that Helicobacter pylori (H. pylori) infection is associated with a higher prevalence of anemia. The aim of this study is to explore this fact for a pediatric population from the northeast of Romania; (2) Methods: A correlational retrospective study between infection with H. pylori and anemia was performed on a group of 542 children in a pediatric gastroenterology regional center in Northeast Romania; (3) Results: Out of 542 children with confirmed H. pylori infection, microcytic hypochromic anemia was present in 48 children, of whom 7 (14.5%) also had iron deficiency.; (4) Conclusions: The study results demonstrate a significant association of H. pylori infection with iron-deficiency anemia and iron deficiency in children in accordance with the results established in the published literature. Although the direct relationship between them it is not clear yet, prevention represents one of the first clinical measures that need to be implemented when encountering a refractory moderate to severe iron-deficiency anemia and, especially, when associated with gastrointestinal tract symptoms.